Analisis Harga Pokok Produksi Berdasarkan Metode Job Order Costing Terhadap UMKM Bandeng Presto Sidoarjo - Whindi Mayrena; Sakina Nur Hayat; Ainur Fahktur Rokhmah; Dian Fahriani (Universitas Maritim AMNI Semarang, 2024)
Presto Milkfish MSME, owned by Ibu Lina, is one of the MSMEs in Indonesia that is growing quickly right now. Founded in 2006, the company currently has three employees. This quick milkfish is a common gift from Sidoarjo. Presto milkfish is frequently served as a side dish to guests during parties. The purpose of this study is to improve knowledge of the cost factors that should be considered when manufacturing pressure-cooked milkfish and to demonstrate how these costs can be added to obtain the appropriate production costs. The job order pricing approach, documentation, and interviews are the data collection techniques employed in this study. At Sidoarjo's Kedung Perku Village Temple, study was conducted.